2021
DOI: 10.1177/08850666211018101
|View full text |Cite
|
Sign up to set email alerts
|

Errors of Commission in Cardiac Arrest Care in the Intensive Care Unit

Abstract: Introduction: Cardiopulmonary arrests (CPAs) are common in the intensive care unit (ICU). However, effects of protocol deviations on CPA outcomes in the ICU are relatively unknown. Objectives: To establish the frequency of errors of commission (EOCs) during CPAs in the ICU and their relationship with CPA outcomes. Methods: Retrospective analysis of data entered into institutional registry with inclusion criteria of age >18 years and non-traumatic cardiac arrest in the ICU. EOCs consist of administration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(28 reference statements)
0
0
0
Order By: Relevance
“…Also, Osmon et al investigation reported 232 medical errors in 728 ICU patients, and 130 (56.2%) of them were commissions or omissions that occurred within the physical location of the ICUs. In their study, most of the medical errors were reported by nurses using SAFE cards (59.1%), and also ICU attending physicians were responsible for 2.6% of medical errors ( 9 , 15 , 16 ). Our research revealed that medical errors in the ICU accounted for 55.8% of all errors, making physician or nurse carelessness the most common.…”
Section: Discussionmentioning
confidence: 94%
“…Also, Osmon et al investigation reported 232 medical errors in 728 ICU patients, and 130 (56.2%) of them were commissions or omissions that occurred within the physical location of the ICUs. In their study, most of the medical errors were reported by nurses using SAFE cards (59.1%), and also ICU attending physicians were responsible for 2.6% of medical errors ( 9 , 15 , 16 ). Our research revealed that medical errors in the ICU accounted for 55.8% of all errors, making physician or nurse carelessness the most common.…”
Section: Discussionmentioning
confidence: 94%